Competitivness of the Czech manufacturing sector in the context of global value chains - Zoller, Martin; Czesaný, Slavoj, 1940-; Damborský, Milan, 1980-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
The thesis analyzes competitiveness of the Czech manufacturing industry in the context of global value chains using data from the OECD TiVA database in years 2000, 2005, 2008 and 2009. The main aim of this work is to highlight the importance of global value chains and outline how the Czech Republic can increase its added value within them. In order to fulfill this objective, the theoretical part explains the importance of global value chains in modern manufacturing industry. In the practical part, five selected industries of the Czech manufacturing sector are compared with the respective industries in Denmark, Finland, Netherlands, Germany and Sweden using indicators of the added value and productivity of production factors. The last section describes the implications and recommendations for the Czech Republic.
Vedoucí práce: Slavoj Czesaný
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses